The game as a forerunner of social values in scholar context - Sena, Silvio; Lima, José Milton de (Brazilian journal of physical education and sport, 2009)
This study has the objective of investigating the game as a forerunner of values in the school context. The aim of this analysis is the incorporation of values like cooperation, solidarity, mutual respect and perseverance by children. In order to do so, this study is based on the Historic-Cultural Theory and on authors who conceive education according to a globalized view. The qualitative methodology has characteristics of intervention, with qualitative and quantitative actions, in the following stages: diagnostic stage; intervention stage 1; and intervention stage 2. In this process, knowledge produced was treated as a descriptive phenomenon. According to the results, there was a decrease in children's physical and verbal levels of aggression; they used the dialogue more frequently, as they needed to solve conflict situations originated in a playing-game context; there was a higher level of respect for the collective decisions; and reduced discrimination and exclusion attitudes. Based on the results of the research and the theoretical framework, this study leads to the conclusion that the game is a social activity, thus, it is important to understand it as an essential component of playing culture enrichment; the Physical Education teacher must have a wide and deep comprehension about the game and children's development; finally, the usage of games in the educational context can be enriched by the quality and frequency of educator's interventions.